Hazards Identification and Risk Assessment In Welding Confined Space Ship Reparation PT. X With Job Safety Analysis Method - Rofiq, Muchammad Aunur; Azhar, Ali (BERKALA SAINSTEK, 2022)
PT X is a docking and shipyard company with experience in repairing various types of ships. Dangers and risks are always exist in every job including ship repair. Therefore, it is necessary to identify hazards and risk assessments. Welding in a confined space includes work that is a source of danger that has the potential to threaten the lives of workers in the ship repair process because access to and exit is limited and is not made to be a continuous work place. The purpose of this study is to identify hazards and assess risks in PT X ship repair confined space welding. The method used in hazard identification and risk control is Job Safety Analysis (JSA) with direct field observations and calculation of likelihood, concequences, and risk values. score on risk assessment according to AS/NZS 4360:2004 and with expert judgment. The results of this study identified that there were 49 potential hazards, then a risk assessment was carried out and there were 36 risks at low risk levels and 13 risks at moderate risk levels. The recommendations given include: using PPE and suction blowers when working, not entering the tank before it is declared safe, taking safety briefings seriously and worker absenteeism, tidying up cables and placing them in a safe position, ensuring workers' hands are dry when in contact with electricity, paying attention to attitude working conditions and conditions around the work area to always be alert